Microsoft Excel Learning Application Design with Android Based using Gamification Method - Permana, Angga; Rizal, Mochamad; gunawan, Dennis (The Indonesian Journal of Computer Science, 2023)
Microsoft excel is software can support performance in data processing, microsoft excel provides formulas and function that can be used to facilitate perfomance in data processing. Utilization of microsoft excel can be used in every day life in business and educational activities. Microsoft excel can perform arithmetic calculation, so can simplifying the assessment results and as an alternative that can provide maximum results. The purpose of this research is design and build a microsoft excel learning application with the gamification method to increase behavioral intention to use and immersion in the learning process to provide an alternative learning process in learning formulas and functions in microsoft excel. The method used in this study was designed and built with the gamification method using the six steps to gamification framework developed by Kevin Werbach in 2016. The results of this learning application have been evaluated by 32 respondents by filling out a survey based on the Hedonic Motivation System Adoption Model. From the survey, 77.5% were obtained for the behavioral intention to use aspect and 64.53% were obtained for the immersion aspect. The conclusion of this study in implementing gamification using the six steps to gamification framework states that they agree with evidence of 77.5% for the behavioral intention to use aspect and 64.53% for the immersion aspect.